Procedural tool for analysing building energy performance: structural equation modelling protocol - SENNAROĞLU, BAHAR (SPRINGER, 2020)
Building energy performance assessment technique has become a new paradigm that plays a significant part in reducing world energy demand and greenhouse gas emissions. However, there exists a global proliferation of diverse models for assessing and benchmarking buildings. This paper proposes a single building energy performance assessment model that considered several factors that affect office building energy efficiency performances in two different countries. It aimed to develop a model that could identify building energy performance critical factors as a new technique for aggregating energy efficiency metrics for commercial buildings. It examined the relationship and interdependency between the variables as it affects buildings' performance as a basis for developing its theoretical model. Survey questions were derived from variables obtained from the existing literature using this theoretical paper proposition. A self-administered questionnaire was used to gather data from occupants of office buildings in Nigeria and the UK. Exploratory factor analysis and structural equation modelling via confirmatory factor analysis were used to analyse the explanatory power of the measured variables and their constructs. The results identified management, strategic and operational issues as critical factors that affect building energy performance in both countries. It confirmed the relationships and interdependency of the study factors and developed a new strategy that gives them proper considerations in the operations and management of building energy. Data collected support the theoretical model, and the measurement model fits into the conceptual model. The model gives a quantitative approach that identified critical factors for improving energy management and auditing efficiency of buildings.
Keywords: Commercial buildings; Climate change; Energy efficiency; Factor analysis; Facilities management; Performance assessment model; CRITICAL SUCCESS FACTORS; ISO 50001; EFFICIENCY; SYSTEM